High-intensity interval training may reduce depressive symptoms in individuals with schizophrenia, putatively through improved VO2max: A randomized controlled trial - Bang-Kittilsen, Gry; Engh, John Abel; Holst, René; Holmen, Tom Langerud; Bigseth, Therese Torgersen; Andersen, Eivind; Mordal, Jon; Egeland, Jens (Frontiers in Psychiatry, 2022)
Introduction High-intensity interval training (HIIT) may improve cardiorespiratory fitness (CRF) and mental health. The current observer-blinded RCT investigates the sparsely studied efficiency of HIIT in reducing psychotic and non-psychotic symptoms in schizophrenia and complements previous studies by investigating whether symptom reduction following HIIT is associated with, putatively partly mediated by, increased VO2max. Methods Participants (outpatients meeting diagnostic criteria for schizophrenia) were randomized to HIIT (n = 43) or a comparison group performing low-intensity active video gaming (AVG) to control for social interaction (n = 39). Both interventions consisted of two supervised sessions/week for 12 weeks and a 4 months follow-up. Effects on overall symptoms and symptom domains [PANSS (0–6 scale), five-factor model] were estimated using mixed-effects models (intention-to-treat, n = 82). Underlying mechanisms were analyzed using moderated mediation analyses (n = 66). We anticipated that HIIT would reduce overall symptoms, particularly depressive symptoms, more than AVG, and symptom reduction would be associated with, putatively mediated through, improved VO2max. Results Depressive symptoms (baseline score 3.97, 95% CI: 3.41, 4.52), were −1.03 points more reduced in HIIT than AVG at post-intervention (95% CI: −1.71, −0.35, p = 0.003), corresponding to a small to moderate effect size (d = 0.37) and persisting at follow-up. There was a small reduction in overall symptoms, but no significant between-group differences were observed. Change in VO2max correlated negatively with the change in depressive symptoms. Mediation analysis showed a significant effect of change in VO2max on change in depressive symptoms within HIIT. The total effect was moderated by group, and depressive symptoms were more reduced in HIIT. Direct effects, not mediated through VO2max, were non-significant. Indirect effects, mediated through VO2max, were non-significant, but the moderated mediation test indicated a non-significant trend of 0.4 points (95% CI: −1.188, 0.087) and a larger reduction in depressive symptoms through VO2max in HIIT. Conclusion HIIT reduced depressive symptoms more than AVG, which persisted at follow-up. HIIT may serve as a complementing treatment option targeting these symptoms in individuals with schizophrenia, even before they reach clinical depression. Depressive symptoms are important to prevent, stabilize, and treat due to their negative implications for psychological wellbeing and long-term functional outcome. Reduction in depressive symptoms was associated with improved VO2max, and non-significant trends in the data supported that improved VO2max may be part of the complex mechanisms underlying the anti-depressive effect of HIIT. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [NCT02205684].